Insider Ownership, Corporate Diversification, and Firm Value: Evidence from REITs. Issue 1 (2nd January 2021) - Talukdar, Bakhtear; Soyeh, Kenneth Wemochiga; Parhizgari, Ali M.
Abstract: We examine the link between REIT insider ownership and property type diversification. Also, we investigate whether property-focused REITs with more insider equity holdings have a higher market value measured by Tobin's Q. REITs provide an ideal setting to study these relations because of the homogeneity in regulations and assets as compared to other securities. Using data from 2003 to 2015, we document that insider ownership has a statistically significant negative impact on property type focus, that this impact is nonlinear, and increases as the extent of insider ownership increases. Further, our findings indicate that REIT insider ownership, in general, is positively related to Tobin's Q and that property type diversified REIT firms with greater insider ownership have higher Tobin's Q. The findings remain qualitatively unchanged even after accounting for time and undertaking robustness checks. Our results are beneficial to investors and portfolio managers in their assessments of future investments in REITs.